2020
DOI: 10.3390/cells9092049
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Caenorhabditis elegans COMPASS in Germline Chromatin Organization

Abstract: Deposition of histone H3 lysine 4 (H3K4) methylation at promoters is catalyzed by the SET1/COMPASS complex and is associated with context-dependent effects on gene expression and local changes in chromatin organization. The role of SET1/COMPASS in shaping chromosome architecture has not been investigated. Here we used Caenorhabditis elegans to address this question through a live imaging approach and genetic analysis. Using quantitative FRET (Förster resonance energy transfer)-based fluorescence lifetime imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 93 publications
2
2
0
Order By: Relevance
“…Although set-2(syb2085) and set-2(bn129) mutants became rapidly sterile at 25°C, set-2(ok952) mutant animals remained fertile, consistent with only a modest loss of H3K4me2/3 in these animals. Sterility in mutants lacking SET-2 catalytic activity may be related to altered chromatin organization or global deregulation of the germline transcriptional program, as we previously observed in the set-2(bn129) mutants (67,68). Interestingly, a similar correlation was not observed between H3K4 methylation and the longevity phenotype, in that all three set-2 mutants showed a reduction in lifespan despite having markedly different global H3K4me2/3 levels.…”
Section: Discussionsupporting
confidence: 58%
“…Although set-2(syb2085) and set-2(bn129) mutants became rapidly sterile at 25°C, set-2(ok952) mutant animals remained fertile, consistent with only a modest loss of H3K4me2/3 in these animals. Sterility in mutants lacking SET-2 catalytic activity may be related to altered chromatin organization or global deregulation of the germline transcriptional program, as we previously observed in the set-2(bn129) mutants (67,68). Interestingly, a similar correlation was not observed between H3K4 methylation and the longevity phenotype, in that all three set-2 mutants showed a reduction in lifespan despite having markedly different global H3K4me2/3 levels.…”
Section: Discussionsupporting
confidence: 58%
“…Although set-2(syb2085) and set-2(bn129) mutants were sterile, set-2(ok952) mutant animals were fertile, consistent with only a modest loss of H3K4me2/3 in these animals. Sterility in mutants lacking SET-2 catalytic activity may be related to altered chromatin organization or global deregulation of the germline transcriptional program, as we previously observed in the set-2(bn129) mutants (56,57). Interestingly, a similar correlation was not observed between H3K4 methylation and the longevity phenotype, in that all three set-2 mutants showed a reduction in lifespan despite having markedly different global H3K4 methylation levels.…”
Section: Discussionsupporting
confidence: 58%
“…Using the RNA-seq data from dissected wild type and oef-1 mutant gonads, we analyzed the frequency of intron retention, which indicates a disruption of normal splicing events. To rigorously define the baseline variation of intron retention that might normally occur between any two independent samples, we established a control comparison between our wild-type sample and an independently collected wild-type dataset, also from dissected gonads ( Herbette et al 2020 ) (Supplementary Figure S10). We then determined the rate of intron retention between oef-1 and our wild-type sample and found that loss of OEF-1 activity led to significantly increased intron retention compared to this control ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“… oef-1 mutants exhibit decreased splicing integrity. (A) Cumulative plot showing an increase in intron retention in oef-1 vs wild type (labeled oef-1 /wt) relative to wild type vs an independent wild type sample ( Herbette et al 2020 ; labeled control, ctl). Differential intron retention [IR, absolute log2 fold change (FC)] is on the x -axis, and accumulated incidence (cumulative frequency) on the y -axis for the oef-1 /wt (red) and control (black) comparisons.…”
Section: Resultsmentioning
confidence: 99%